Uncomfortable bedfellows: Employer perspectives on general practitioners’ role in the return-to-work process - Kosny, A.; Brijnath, Bianca; Singh, N.; Allen, A.; Collie, A.; Ruseckaite, R.; Mazza, D. (I O S H Publishing, 2015)
Workers’ compensation authorities expect that various stakeholders – insurers, employers, injured workers and healthcare providers – work together to help return an injured worker to early, safe and sustainable employment. To date, research examining interactions between employers and healthcare providers, in the context of return to work, is limited. Based on data gathered via qualitative, in-depth interviews with employers, our paper addresses this gap. We examine the perspectives of a group of employers from Melbourne, Australia who have had experience with return to work and, specifically, their interactions with general practitioners during this process. Our findings indicate that while employers view general practitioners as important decision-makers in the return-to-work process, they often have difficulty making contact with general practitioners and working collaboratively on a return-to-work plan. They feel that general practitioners’ lack of engagement in the return-to-work process is due to the administrative complexity of the workers’ compensation system, limited remuneration and lack of knowledge of the workplace. Employers’ feelings of exclusion, along with a view that some injured workers will ‘cheat the system’, make some employers suspicious of the doctor–patient relationship, making collaboration more difficult. Including employers in an employee’s return to work can signify that they have influence over processes that can profoundly affect their workplaces and provide decision-makers with important information about available duties and workplace organisation. Streamlined administrative processes, higher remuneration for general practitioners and the engagement of return-to-work coordinators can also facilitate the return-to-work process.